The relative age effect in successful national football teams - Isin, A. (Kinesiologia Slovenica, 2021)
The aim of the present study was two-fold; (1) to examine the relative age effect of football players representing their countries and reaching the podium in the FIFA U17 and U20 World Cups between 2009 and 2019, and (2) to analyze the relative age effect according to players` positions. This study was a retrospective cross-sectional design. A total of 756 male football players were included in the study. Dates of birth of football players were grouped into periods of three months in a quartile year. All data is presented in frequency and percentage. Chi-square was applied to determine differences in the inter-group distributions. The odds ratio, confidence interval (95%) and Cramer`s V were calculated. The findings emphasized the relative age effect in successful national teams participating last six U17 and U20 World Cup. The relative age effect of U17 was higher compared to U20 (?² = 70.974; p < 0.001, ?² = 39.587; p < 0.001 respectively). As a result of the research, players born in the first quartile of the year have been represented on podium more than those born in the last quartile, significantly. The findings of this study confirm the presence of relative age effect among football players reaching the podium in the last six U17 and U20 World Cup. Coaches and sports scientists are suggested to take the relative age effect into reconsideration to reduce this bias and to improve the system leading to loss of talents as a consequence.